Effectiveness of Sexual Skills Training Program on Promoting Sexual Intimacy and Satisfaction in Women in Tehran (Iran): A randomized clinical Trial Study - Salehi Moghaddam, Fatemeh; TorkZahrani, Shahnaz; Moslemi, Azam; Azin, Seyyed Ali; Ozgoli, Giti; Joulaee Rad, Narges (Urology Journal, 2020)
Purpose: The purpose of this study was to evaluate the effectiveness of sexual skills training on intimacy and sexual satisfaction in women. Materials and Methods: This is a randomized clinical trial study with parallel design. 70 participants (n=35 each) were divided into 2 groups as control and intervention groups. Women were selected in multiple steps. Some requirements for inclusion criteria were: obtaining a standard score of marital satisfaction, women with a record of 6-24 months of marital life, not having a record of abortion, stillborn birth and not being in pregnancy period, not having a child, not suffering from an acute or chronic and serious disease, not having a surgery on pelvic organs, minimum elementary education of the couples and being Iranian. Some factors for exclusion criteria were: women’s absence in more than 2 training classes, pregnancy during the study. Data collection was conducted through four questionnaires: demographic characteristics, marital satisfaction, sexual satisfaction and sexual intimacy. Validity and reliability of the questionnaires were measured through content validity and Chronbach Alpha, respectively. The data extracted from the questionnaires were analyzed using SPSS software, version 18.0. For data analysis, descriptive statistics, independent t-test, paired t-test, or non-parametric tests were applied. Significance level of the test was considered p<0.05. Results: The results showed that sexual skills training leads to promotion of sexual satisfaction (p<0.001) and sexual intimacy (p<0.001) among the women in intervention group and the impact of training was stable two months after completion of intervention. Conclusion: In total, the training lessons gave positive views to participants towards their sexual issues so that they formed realistic and positive sexual expectations, healthier sexual behaviors and self-expressions and consequently, gained more sexual knowledge that made them able to experience more intimacy and satisfaction in sexual relationships with their spouses.